Foreign Relations in Brazilian Federal Units: An Analysis of Expenditures and Political Parties - Prins, Ricardo Margalho (Conjuntura Global, 2015)
Through analysis of official documents, this paper addresses the field of International Relations of subnational entities. It aims to verify the following hypothesis, proposed in the conclusion of a well-known article in the area: Is the external action of subnational governments in Brazil more intense in federal units where the dominant political coalition matches the dominant political coalition in the central government? Keywords: Paradiplomacy; Political Parties; Subnational Governments.